EXPLORING THE USE OF MEDIA IN TEACHING SPEAKING - Edy Waloyo; Lona Fatekha (Universitas Islam Ogan Komering Ilir Kayuagung, 2022)
This research aims to explain the kind of media and the advantages and disadvantages of media the process of teaching speaking at Senior High School 1 Gegesik Cirebon. This research used a qualitative method using descriptive qualitative. The instrument of this research is the researcher herself. To collect the data, the researcher used interviews. Interview technique used to answer the first and second question. The result shows that: (1) Visual material, such as textbooks, auditory media, such as songs, and audiovisual media, such as movies and videos, as well as digital media, such as YouTube, were all used by the teacher. (2) The advantages of using media in teaching and learning speaking are students understand the material easily, make the students interested in the learning process and the students become more active to practice their speaking by giving comment, question, and answering the question. On the other hand, the disadvantages of using media are noisy class, students feeling shy, and the student’s loss of control